Introductory solid state physics with MATLAB applications - Hasbun, Javier E.; Datta, Trinanjan (NewYork: CRC Press, 2020)
"Solid state physics, the study and prediction of the fundamental physical properties of materials, forms the backbone of modern materials science and has many technological applications. The concepts learned in solid state physics also play an important role in treating systems that deviate away from the solid state, namely, glasses and perhaps even liquids for those who pursue such condensed matter topics. The unique feature of this text is the MATLAB-based computational approach with several numerical techniques and simulation methods included"--Back cover.
Introduction -- The reciprocal lattice -- Crystal binding -- Lattice vibrations -- Free electron gas -- Introduction to electronic energy bands -- Semiconductor crystal properties -- Simple band structure calculations -- Impurities and disordered systems -- Magnetism I -- Magnetism II -- Superconductivity -- Optical properties of solids -- Transport properties of solids -- Appendix A: MATLAB TUTORIAL -- Appendix B: Distribution functions.
Includes bibliographical references and index.
Keywords: Solid state physics; Crystals; Physics -- Textbooks; Crystals; Physics; Solid state physics